2011
DOI: 10.1007/s00198-010-1516-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of comorbidity measures for predicting outcomes in population-based osteoporosis cohorts

Abstract: Recommendations about the optimal comorbidity measure will vary with the outcome under investigation. Overall, the Elixhauser index performed well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
(57 reference statements)
0
24
0
1
Order By: Relevance
“…Based on an extensive review, Sharabiana et al [23] found that if a comorbidity measure were necessary, the Elixhauser comorbidity score might be the best choice, but they had reservations that the results might differ based on the patient group and the outcome being investigated. However, one must consider that predictive performance of all the comorbidity index scores was not only outcome; the risk-adjustment method also had bearing [17], as was seen in patients with osteoporosis [6,15]. Based on our results, we conclude that if consideration of patient comorbidities is necessary to achieve a particular purpose, then the Elixhauser comorbidity score would seem the best for predicting patient HRQoL, pain, and satisfaction 1 year after THA.…”
Section: Discussionmentioning
confidence: 69%
“…Based on an extensive review, Sharabiana et al [23] found that if a comorbidity measure were necessary, the Elixhauser comorbidity score might be the best choice, but they had reservations that the results might differ based on the patient group and the outcome being investigated. However, one must consider that predictive performance of all the comorbidity index scores was not only outcome; the risk-adjustment method also had bearing [17], as was seen in patients with osteoporosis [6,15]. Based on our results, we conclude that if consideration of patient comorbidities is necessary to achieve a particular purpose, then the Elixhauser comorbidity score would seem the best for predicting patient HRQoL, pain, and satisfaction 1 year after THA.…”
Section: Discussionmentioning
confidence: 69%
“…The Elixhauser comorbidities index [12] has been used frequently in previous studies using NIS data [11,17,29]. Based on recent studies, the Elixhauser comorbidity index performs well in predicting outcome of patients [5,9,22] and based on the recent systematic review performed by Sharabiani et al [27], the Elixhauser comorbidity index seems to be one of the best comorbidity indexes for predicting outcome of patients in administrative databases. Therefore, we decided to use this comorbidity index in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Although many scoring systems have been desig- ned for hip fractures, CCI seems to be the frequently used in the prediction of mortality following fracture surgery 7,9,20,21 . In a study by Kirkland et al, 22 on hip fractures in elderly patients, a strong relationship was found between a CCI score of >6 and 30-day mortality rates but no comment was made about sensitivity or specificity of CCI scoring system.…”
Section: Discussionmentioning
confidence: 99%